Responding to the increased genetic risk associated with customary consanguineous marriage among minority ethnic populations: lessons from local innovations in England - Salway, Sarah (J Community Genet, 2016)
Populations practising customary consanguineous marriage have a higher incidence of autosomal recessive genetic disorders than those in which reproductive partners are usually unrelated. In the absence of any national-level response, English service developments to address the additional needs of families living with or at risk of such disorders have been locally led. These interventions remain in their infancy here, as elsewhere in Europe, and important questions remain regarding how appropriate, effective and sustainable responses can be operationalised in practice. This formative service review employed four local case studies together with wider consultation exercises over a 4-year period (2011–2015) to document recent responses to this area of need, issues arising and lessons to inform future work. Service components included the following: enhancements to genetic services to provide family-centred, culturally competent approaches to counselling and testing; community genetic literacy approaches; and capacity development among health professionals. Local approaches were, however, very varied in their detail, scope, level of investment and longevity. The provisions of culturally competent genetic counselling services and community-level genetic literacy interventions were generally well received by those who accessed them. Coordinated action across all service components appeared important for an effective service, but healthcare professionals, particularly general practitioners, were often difficult to engage in this agenda. An evaluative culture and engagement in a wider community of practice had supported service development across sites. However, sustaining investment was challenging, particularly where new services were not well integrated into core provision and where commissioning was driven by expectations of short-term reductions in infant mortality and disability.